A Process Discovery and Conformance Checking Integration System for the Optimization of Resources in the Application of Process Mining - Marin, Enrique Martin Saqui (2023)
In this paper, we present a novel system that combines process discovery and conformance checking to optimize resource usage in the operations area of banking companies. Our proposed system improves upon previous solutions by integrating real-time process mining techniques to reduce resource consumption in banking operations. The use of real-time process mining techniques in the proposed system enables faster error identification in processes, emphasizing the importance of such techniques for banking companies. The system is comprised of two integrated process mining techniques, as reported in existing literature. Process discovery involves two key components: dataset generation and process visualization. Additionally, compliance checking involves process monitoring, alerts, and reports. To validate the effectiveness of our system, we conducted a stress test, which was evaluated by experienced process mining users with extensive experience in the banking sector in Lima, Peru. Preliminary results of the stress test demonstrated a significant improvement in system performance, with a 37.42% increase in the capacity of web requests per minute and a total of 82.86% of requests successfully answered. These results enabled corrective and preventive actions to be taken, indicating the practical value of our proposed system in optimizing resource usage in banking operations. In conclusion, our system provides a robust solution to optimize resource usage in the operations area of banking companies and emphasizes the importance of real-time process mining techniques in achieving this goal. The system has been validated through a stress test and evaluation by experienced users in the banking sector, further indicating its practical applicability.